Alumosilicate ceramic proppants based on natural refractory raw materials; IOP Conference Series: Materials Science and Engineering; Vol. 286 : Modern Technologies and Materials of New Generations (MTMNG-2017) - Vakalova T. V. Tatyana Viktorovna; Devyashina L. P. Larisa Pavlovna; Burihina M. A.; Kisner A. S.; Pashenko N. V. (2018, 2018)
Title screen